Laparoscopic Technique for Serial Collection of Para-Colonic, Left Colic, and Inferior Mesenteric Lymph Nodes in Macaques - Smedley, Jeremy (PLoS One, 2016)
Unlike peripheral lymph nodes (PLN), the mesenteric lymph nodes (MLN) draining the gastrointestinal (GI) tract are exposed to microbes and microbial products from the intestines and as such, are immunologically distinct. GI draining (MLN) have also been shown to be sites of early viral replication and likely impact early events that determine the course of HIV infection. They also are important reservoir sites that harbor latently-infected cells and from which the virus can emerge even after prolonged combination antiretroviral therapy (cART). Changes in the microbial flora and increased permeability of the GI epithelium associated with lentiviral infection can impact the gut associated lymphoid tissue (GALT) and induce changes to secondary lymphoid organs limiting immune reconstitution with cART. Nonhuman primate models for AIDS closely model HIV infection in humans and serial sampling of the GALT and associated secondary lymphoid organs in this model is crucial to gain a better understanding of the critical early events in infection, pathogenesis, and the role of immune responses or drugs in controlling virus at these sites. However, current techniques to sample GI draining (MLN) involve major surgery and/or necropsy, which have, to date, limited the ability to investigate mechanisms mediating the initiation, persistence and control of infection in this compartment. Here, we describe a minimally invasive laparoscopic technique for serial sampling of these sites that can be used with increased sampling frequency, yields greater cell numbers and immune cell subsets than current non-invasive techniques of the GALT and reduces the potential for surgical complications that could complicate interpretation of the results. This procedure has potential to facilitate studies of pathogenesis and evaluation of preventive and treatment interventions, reducing sampling variables that can influence experimental results, and improving animal welfare.